PENGUATAN PERKEMBANGAN MORAL SISWA PADA PROSES PEMBELAJARAN MELALUI HIDDEN CURRICULUM DI KELAS IV SDN 1 PURBALINGGA WETAN PURBALINGGA: Penelitian Deskriptif - Hidayati, Aisyatul; Andriani, Ana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The cultivation of moral values in schools plays a crucial role in shaping students' character. This study aims to analyze the strengthening of students' moral development through the hidden curriculum in Grade IV at SDN 1 Purbalingga Wetan. Using a qualitative approach and phenomenological method, data were collected through observation, interviews, and documentation. The findings indicate that teachers play a central role in instilling moral values through exemplary behavior, daily routines, and reflective and collaborative activities. Values such as honesty, discipline, responsibility, empathy, and tolerance are instilled through activities like classroom duties, group prayers, and discussions. A well-ordered and supportive school environment further reinforces character development. Supporting factors include consistent school routines and culture, while challenges involve limited parental support and the influence of digital media.